Hasil Pemeriksaan Biomarker Fungsi Ginjal Pada Penderita Diabetes Melitus Ditinjau Dari Lama Menderita Dan Hasil Pemeriksaan HbA1c - Yaumil Fachni Tandjungbulu; Alfin Resya Virgiawan; Rahman Rahman; Muhammad Ade Luthfi; Haerani Haerani (Direktorat Politeknik Kesehatan Makassar, 2023)
Diabetic nephropathy is a complication that occurs in Diabetes Mellitus (DM) sufferers which is characterized by a decrease in kidney function. Current laboratory examination biomarkers to determine the condition of kidney function that are often carried out in the laboratory include examination of urea, creatinine, and urine protein. One way that can be done to determine blood glucose control is through HbA1c examination. This study aims to see the correlation between the results of kidney function biomarker examinations (urea, creatinine, and urine protein) in DM sufferers in terms of length of suffering (<5 years, 5-10 years, 11-16 years, and >16 years), as well as the results HbA1c examination. This research uses a correlative research method with an approach cross sectional analytically, the number of samples was 90 samples that met the research inclusion criteria. Sample collection and examination was carried out at the Clinical Pathology Laboratory of Hasanuddin University Hospital, Makassar from 8 to 15 May 2023. The research results showed that there was a significant relationship between the results of urine protein examination with a value of p=0.018 (p<0.05) and the duration of suffering and the results of the HbA1c examination in DM sufferers, and there was no significant relationship between the results of the urea examination p=0.352 (p>0.05) and creatinine p=0.116 (p>0.05) with the length of suffering and the results of the HbA1c examination in DM sufferers, so it can be concluded that urine protein is a potential biomarker in laboratory examinations to see the risk of complications of kidney damage in DM sufferers. It is recommended that DM sufferers carry out regular kidney function checks to reduce the risk of complications in the long term. Keywords: Creatinine, Diabetes Mellitus, HbA1c, Urea, Urine Protein